A new series of heteronuclear metal strings, MRhRh(dpa)4Cl2 and MRhRhM(dpa)4X2, from the reactions of Rh2(dpa)4 with metal ions of group 7 to group 12. Issue 2 (18th December 2020) - Cheng, Ming-Chuan; Lee, Gene-Hsiang; Lin, Tien-Sung; Liu, Yu-Chiao; Chiang, Ming-Hsi; Peng, Shie-Ming
Abstract : A new series of trinuclear and tetranuclear HMSCs, MRhRh(dpa)4 Cl2 and MRhRhM(dpa)4 X2, from the reactions of Rh2 (dpa)4 and metal ions were synthesized. Abstract : We report the syntheses, structures, magnetic and electrochemical properties of MRhRh metal cores helically wrapped by four dpa − (2, 2′-dipyridylamide) ligands. We successfully synthesized the precursor Rh2 (dpa)4 (1 ) in high yield and characterized its structure including its oxidized form (1 + ) which facilitated the syntheses of this series of metal springs. By the reactions of (1 ) and the metal ions of group 7 to group 12 (M = Mn(2 ), Fe(3 ), Co(4 ), Ni(5 ), Cu(6 ), Pd(8 ), Pt(9 ), Ru(10 ), Ir(11 ) and Rh(12 )), ten MRh2 (dpa)4 Cl2 complexes were successfully isolated. Note that Cd(7 ) can only be obtained by the one-pot method. The yield of Rh3 (dpa)4 Cl2 (12 ) is also improved by this stepwise method. The oxidized complexes [MRh2 (dpa)4 Cl2 ](PF6 ) (M: Ni(5 + ), Ru(10 + ), Ir(11 + )) are also synthesized for the studies of electronic structures and magnetic properties. The X-ray diffraction technique is applied to characterize all of their structures. The results of these structural, magnetic, and electrochemical studies provide us with in-depth knowledge and comprehensive insight into metal–metal bonds and interactions for this new series of metal strings. In particular, four metal–metal bonds with short distances are found: Pd–Rh (2.372(13) Å), Pt–Rh (2.385(7) Å), Ru–Rh (2.33(3) Å), and Ir–Rh (2.373(5) Å). The remaining ones show no evidence of covalent metal bonds judging from their metal–metal distances, magnetic behaviour, and redox couples in electrochemical analysis. Besides, two unique tetranuclear MRhRhM(dpa)4 X2 (M: Cu + (13 ) and Ag + (14 )) complexes with a Rh2 (dpa)4 framework are developed. Four metals are aligned linearly. This coordination mode of metal strings provides a unique synthetic route for constructing longer metal chains from a smaller number of dentate ligands.